PUTUSAN MAHKAMAH KONSTITUSI NOMOR 53PUU-XV2017 SEBUAH PERJALANAN MENJADI PESERTA PEMILU 2019 - Edho Rizky Ermansyah (Universitas Negeri Semarang, 2020)
Political parties have a long way to go to be seen as election participants. Some several stages and mechanism must be taken: registration, administrative research, factual levers. The construction of political party registration for the 2019 general election is regulated in Article 173 paragraph (1) and 173 paragraph (3) of Law Number 7 of 2017 concerning General Election. The two provisions of the norm of the article are then subject to review at the Constitutional Court. The Petitioner in this case is the Ideal Party represented by the General Chairman. The Constitutional Court then granted the petitioner's petition partially with the articles being tested as long as the phrase “already determined” in Article 173 paragraph (1) does not have binding legal force and Article 173 paragraph (3) has no binding legal force